2018
DOI: 10.1093/biolre/ioy158
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the expression of the renin-angiotensin system in the myocardium of mice conceived by in vitro fertilization†

Abstract: Epidemiological studies have revealed that offspring conceived by in vitro fertilization (IVF) have an elevated risk of cardiovascular malformations at birth, and are more predisposed to cardiovascular diseases. The renin-angiotensin system (RAS) plays an essential role in both the pathogenesis of congenital heart disease in fetuses and cardiovascular dysfunction in adults. This study aimed to assess the relative expression levels of genes in the RAS pathway in mice conceived using IVF, compared to natural mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…Epidemiological studies have described that any defects during epigenetic reprogramming, including the imprinting process, may increase the risk of genetic and epigenetic disorders [ 44 , 45 ]. Mouse models have been used to study and observe embryonic abnormalities and offspring diseases [ 46 , 47 ], but the precise molecular mechanisms underlying these malformations remain unclear. It is a limit that congenital birth defects were based on telephone interviews; besides, the birth defects may need further genetic testing and phenotypic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have described that any defects during epigenetic reprogramming, including the imprinting process, may increase the risk of genetic and epigenetic disorders [ 44 , 45 ]. Mouse models have been used to study and observe embryonic abnormalities and offspring diseases [ 46 , 47 ], but the precise molecular mechanisms underlying these malformations remain unclear. It is a limit that congenital birth defects were based on telephone interviews; besides, the birth defects may need further genetic testing and phenotypic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have found endothelial dysfunction and hypertension in IVF-produced mice offspring [ 44 , 45 ], which could be associated with risk of premature cardiovascular morbidity. Moreover, ART-produced female offspring showed altered expression of the renin-angiotensin system, which regulates blood pressure and is known to play a role in the pathogenesis of CVD [ 46 ]. Several experimental studies in mouse have demonstrated that ART can alter glucose metabolism, from simple hyperglycaemia to impaired glucose tolerance, which can lead to hyperinsulinemia and in some cases, to insulin resistance [ 36 , 47–49 ].…”
Section: Art and Metabolic Alterationsmentioning
confidence: 99%
“…It is evident that ART procedures affect metabolic health and disease in a sex-specific manner. Female ART-conceived offspring are more susceptible to cardiovascular alterations and obesity at a young age than their counterpart male offspring [ 42 , 46 ]. However, in male offspring, the alterations become more evident later in life, suggesting the possible risk of further disease development [ 36 , 42 ].…”
Section: Phenotypical Plasticitymentioning
confidence: 99%
“…Recently, the effect of ART on the angiotensin II receptors (AT1R and AT2R) has gained attention. Wang and colleagues found increased cardiac AT1R mRNA expression in ART mice starting the third week after birth and persisting for as long as 1.5 years [ 9 ]. Moreover, Zhang and colleagues reported partial hypomethylation of the At1bR gene in the umbilical vein of human ART [ 10 ].…”
Section: Introductionmentioning
confidence: 99%